2022
DOI: 10.31234/osf.io/w6x4t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scanpath Regularity as an Index of Reading Comprehension

Abstract: Purpose: Recent research on the potential of using eye-tracking to measure reading comprehension ability suggests that the relationship between standard eye-tracking measures and reading comprehension is influenced by differences in task demands between comprehension assessments. We compared standard eye-tracking measures and scanpath regularity as predictors of reading comprehension scores. Method: We used a dataset in which participants were administered three widely-used reading comprehension assessments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The first step of the analysis was to generate and cluster scanpaths to identify the global reading patterns that participants used when reading passages of text that contained ironic and literal statements. This part of the analysis was carried out in the same way for the two datasets (i.e., Kaakinen et al, 2014, Exp 2;Olkoniemi et al, 2016) separately, and follows the same steps used in previous studies investigating reading strategies and individual differences using scanpaths (e.g., Mézière et al, 2022;Parshina et al, 2022;von der Malsburg & Vasishth, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first step of the analysis was to generate and cluster scanpaths to identify the global reading patterns that participants used when reading passages of text that contained ironic and literal statements. This part of the analysis was carried out in the same way for the two datasets (i.e., Kaakinen et al, 2014, Exp 2;Olkoniemi et al, 2016) separately, and follows the same steps used in previous studies investigating reading strategies and individual differences using scanpaths (e.g., Mézière et al, 2022;Parshina et al, 2022;von der Malsburg & Vasishth, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, these distinct patterns and strategies could not have been identified with standardly used word-level measures, showing that scanpaths can capture features of eye-movement behavior not caught by word-level measures. In addition, they found that readers' re-reading behavior and the extent to which they use those three strategies interacted with their WMC, showing that scanpaths are also useful to investigate the role of individual differences in processing strategies used during reading (see also Mézière et al, 2022;Parshina et al, 2022). Hence, scanpaths provide an ideal tool to investigate the strategies readers use in the processing written irony, as well as the role of individual differences such as WMC or comprehension accuracy in reading literal and ironic passages of text.…”
Section: Scanpath Analyses Of Eye Movement Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Admittedly, reading fluency per se is not a direct index of reading skill or successful comprehension: A text can be skimmed fast but poorly understood (Strukelj and Niehorster, 2018). Moreover, eye movements while reading depend not only on reading skill but also on reading goals and task demands (Mézière et al, 2021(Mézière et al, , 2022. For these reasons, we approximate reading skill through a combination of two measures: scanpaths, a combined measure capturing eye movements while reading, and questions probing sentence comprehension.…”
Section: The Present Studymentioning
confidence: 99%